STRATEGIES OF ARCHIVES AND LIBRARY SERVICES IN INCREASING INTEREST AND READING CULTURE OF THE COMMUNITY IN WEST BANDUNG REGENCY - Cressa Rara Say; Nandang Alamsah Deliarnoor; Rina Hermawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the strategies implemented by the Archives and Library Office of West Bandung Regency in increasing public interest and reading culture. This study uses qualitative research methodology by using in-depth interviews, observation and document analysis as data collection techniques. The focus of the study included program identification, supporting factors and barriers in the implementation of literacy strategies. The key strategies implemented as a result of the study include the revitalization of Taman Bacaan Masyarakat (TBM), procurement of book collections of 11,612 titles and 47,035 copies, introduction of digital library services, and literacy campaigns through social media and local communities. contains Community. However, there are several obstacles that hinder the optimization of the program such as budget limitations, low community participation in literacy activities and the lack of qualified managers. Factors that support the implementation of this strategy include political support from the local government and the possibility of collaboration with various communities. This study recommends strengthening technology-based literacy programs, increasing the budget for purchasing reading materials and training library managers as strategic steps to overcome these obstacles. The results are expected to make a practical contribution to more innovative and sustainable literacy policies and serve as a reference for developing literacy strategies in other areas. Literacy is seen as an important element in supporting human resource development in West Bandung district.